A qualitative study exploring adolescents' experience of brief behavioural activation for depression and its impact on the symptom of anhedonia. (12th September 2020) - Watson, Rebecca; Harvey, Kate; Pass, Laura; McCabe, Ciara; Reynolds, Shirley
Abstract : Objectives: Anhedonia, the loss of interest and pleasure, is a core symptom of depression and is associated with deficits in reward processing. Behavioural Activation for depression may address this symptom due to its focus on identifying and increasing intrinsically rewarding activities. Design: This was a qualitative study employing reflexive thematic analysis (TA). Methods: Participants were eight treatment‐seeking adolescents with a recent primary diagnosis of depression who had received eight sessions of Brief Behavioural Activation. Qualitative semi‐structured interviews were conducted after treatment was completed. Results: Three main themes emerged: (1) connecting, reviewing, and taking action: 'focus on getting better rather than what you're feeling'; (2) struggles, restrictors, and motivators: 'it seemed really unachievable'; and (3) feeling, acting, or seeing things differently: 'looking forwards in a more healthy way'. Conclusions: Both specific Brief Behavioural Activation strategies (e.g., connecting with values) and more generic therapeutic strategies (e.g., self‐monitoring) may be helpful in treating the symptom of anhedonia in adolescent depression. Motivational aspects of anhedonia, as well as anxiety, fatigue, and academic pressures act as potential barriers to recovery. This highlights the need for psychological treatments for adolescent depression to include explicit and targeted strategies to enhance motivation. Practitioner points: Young people reported that specific Brief Behavioural Activation strategies (e.g., connecting with values) and more generic therapeutic techniques (e.g., self‐monitoring) had a role in treating anhedonia. Barriers to engaging in Brief BA included: motivational anhedonia, fatigue, and academic demands.